Screening of Mycotoxin Produced by Fusarium Verticillioides and F. Proliferatum in Culture Media - Matny, Oadi N (Asian Journal of Agriculture and Rural Development, 2014)
This study was conducted to evaluate the production of mycotoxin by Fusarium verticillioides and Fusarium proliferatum strain in culture media. Results of Fusarium strain speciation by sequencing technique for the αTEF gene regent showed that 16 isolates from 21 belong to F. verticelloides, four to F. proliferatum and one to Fusarium solani. Mycotoxin production test showed that all Fusarium strains obtained produce different levels of T2-toxin, DON, ZEN and fumonisin in culture media with fumonisin toxin having the highest chemotype produced.